2017
DOI: 10.1108/el-12-2015-0239
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ social reading: motivation, behaviour, and their relationship

Abstract: Purpose Using the case of social reading via WeChat in China, this paper aims to explore adolescents’ social reading motivation and behaviour. It also examines how the specific dimensions of reading motivation contribute to the different aspects of social reading behaviour. Design/methodology/approach This study used survey approach, which gathered 1,039 valid responses from a cluster sampling in 14 middle and high schools in Shanghai, China. Findings The results indicated that social reading motivation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
2
6
0
2
Order By: Relevance
“…First, studies have shown that reading activities can enrich spirituality, kill time, and promote self-development. However, spiritual abundance and the loneliness of reality often produce a strong sense of gap and increase the inner social interaction needs of an individual, thereby stimulating individual's motivation for social interaction ( 21 ). Wang found a significantly positive correlation between individual reading activities and social activities ( 22 ).…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%
“…First, studies have shown that reading activities can enrich spirituality, kill time, and promote self-development. However, spiritual abundance and the loneliness of reality often produce a strong sense of gap and increase the inner social interaction needs of an individual, thereby stimulating individual's motivation for social interaction ( 21 ). Wang found a significantly positive correlation between individual reading activities and social activities ( 22 ).…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%
“…Bu durumda söz konusu uygulamaların okurlar için okuma sürecini daha sosyal bir süreç hâline getirebileceği söylenebilir. Nitekim Li & Wu, (2017) okumanın, dijital ortamların kullanımı ile birlikte düşüncelerin, görüşlerin, okunanlardan alıntıların paylaşıldığı daha sosyal bir etkinlik hâline geldiğine vurgu yapmıştır. Bu şekilde söz konusu uygulamaları kullanan okurlar kitap seçerken birbirlerine yardımcı olma, kitaplar hakkında birbirleri ile görüş ve bilgi alışverişinde bulunma şansı elde edebilir.…”
Section: Tartışma Ve Sonuçunclassified
“…The social aspect of social media prominently influenced students' digital literacy. Interacting with peers created communities that empowered students to more confidently participate (Vikneswaran & Krish, 2016) and added extrinsic motivation to online reading that is not typical of offline texts (Li & Wu, 2017). Questions regarding how to utilize the social benefits of social media also surfaced: Should students use informal diction when posting to social media for class?…”
Section: Social Literacymentioning
confidence: 99%